2018
DOI: 10.1186/s42358-018-0007-y
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Brazilian version of the Hip Outcome Score (HOS) questionnaire

Abstract: Background: The Hip Outcome Score (HOS) was developed to evaluate physically active patients with hip disease but without severe degenerative change. A translation and cultural adaptation into Brazilian Portuguese was previously conducted. The aim of this study was to validate the Brazilian version of the HOS (HOS-Brazil) among a group of physically active patients with a diagnosis of femoroacetabular impingement (FAI) or greater trochanteric pain syndrome (GTPS). Methods: The following questionnaires were app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…The test–retest reliability was reported in a single study and found to be 0.99 (95% CI 0.99 to 1.00) for the HOS-Brazil (ADL) and 0.99 (95% CI 0.99 to 1.00) for the HOS-Brazil (Sport) 23. The HOS-Brazil subscales (ADL and Sport) were rated down due to indirectness, as the study included patients without gluteal tendinopathy (37% had femoroacetabular impingement), and one level for both risk of bias and imprecision (n<100) 23. Overall, there was very low-quality evidence of sufficient test–retest reliability of the HOS-Brazil (ADL) and the HOS-Brazil (Sport) (table 3).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The test–retest reliability was reported in a single study and found to be 0.99 (95% CI 0.99 to 1.00) for the HOS-Brazil (ADL) and 0.99 (95% CI 0.99 to 1.00) for the HOS-Brazil (Sport) 23. The HOS-Brazil subscales (ADL and Sport) were rated down due to indirectness, as the study included patients without gluteal tendinopathy (37% had femoroacetabular impingement), and one level for both risk of bias and imprecision (n<100) 23. Overall, there was very low-quality evidence of sufficient test–retest reliability of the HOS-Brazil (ADL) and the HOS-Brazil (Sport) (table 3).…”
Section: Resultsmentioning
confidence: 96%
“…One study reported the minimal detectable change of the HOS-Brazil (ADL) and HOS-Brazil (Sport), which were 4.71 and 5.27, respectively (table 4). 23 The minimal important change of the HOS-Brazil (ADL) and (Sport) in patients with gluteal tendinopathy was 4.6 and 5.5, respectively 23. Overall, there was very low-quality evidence that the measurement error of the HOS-Brazil (ADL) was insufficient and very low-quality evidence that the measurement error in the HOS-Brazil(Sport) was sufficient.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of 803 articles found, 20 full texts were assessed for eligibility27–46 and 10 studies were included in the qualitative synthesis 27 28 32 36 37 39–41 45 46. The flow chart of the literature search for the updated SR is presented in figure 2.…”
Section: Methodsmentioning
confidence: 99%